Revolutionary Writings : Reflections on the Revolution in France and the First Letter on a Regicide Peace - Burke, Edmund, 1729-1797.; Hampsher-Monk, Iain, 1946-; Burke, Edmund, 1729-1797.; Burke, Edmund, 1729-1797. (New York : Cambridge University Press, 2014)
"Burke's Reflections on the Revolution in France was the first sustained theoretical critique of the French Revolution; and is now recognised as the classic statement of modern conservatism. Reflections surveys the British political culture of traditionalism, gradualism and deference, and contrasts it with the French Revolutionaries' programme of appeal to abstract right, transformational change and popular agency. Ultimately Burke advocated a counterrevolutionary war and the restoration of the French monarchy. This accessible new edition brings together for the first time Burke's first and last published thoughts on the revolution including as it does the first Letter on a Regicide Peace; a work that has contributed to a particular view of international society. Featuring a comprehensive introduction and extensive annotations, Iain Hampsher-Monk's edition helps readers new to Burke to better understand the historical, political and philosophical context behind his writings, and the significance of contemporary and classical allusions"--
"Burke's Reflections has long been seen as an epitomic text, supposedly articulating an - indeed the first - theoretical defence of 'modern conservatism'. In keeping with the philosophy of the Series, this edition seeks to place it in the intellectual contexts in which its author conceived and wrote it, whilst also indicating those in which it came to be read. Alongside Reflections - Burke's early response to the Revolution - is included one of his last, the first Letter on a Regicide Peace, a work that reveals the development of his thought during the course of the Revolution and one that has helped to shape a particular view of international society"--
Machine generated contents note: Preface; Acknowledgements; Editor's introduction; Further reading; Chronology; Notes; A note on the texts; Reflections on the Revolution in France; The first Letter on a Regicide Peace; Appendix A (variant reading from A Regicide Peace); Index.
Includes bibliographical references and index.
Keywords: Burke, Edmund, -- 1729-1797 -- Correspondence; POLITICAL SCIENCE / General; France -- History -- Revolution, 1789-1799 -- Causes; France -- Politics and government -- 1789-1799 -- Foreign public opinion, British